Analisis Dan Perancangan Sistem Slip Gaji Dan Rekap Absen Di Kedai Kopi Pojok Pamulang - Angga Firnanda Yuda; Aulia; Jihan Nur Haniyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The problem of payroll is a complicated problem, because this problem does not only involve a few rupiahs of an employee who must be paid for his work, but also has wide implications in terms of the wage system and employee attendance recap. This is an obstacle in the corner coffee shop Pamulang in a Coffee Shop must have employees, where every month they will receive a salary as a reward to be paid to employees for their services or work at a Coffee Shop. This website is designed using HTML, JS, and CSS. The research method used is the waterfall method.